Magnetic phase diagram of CrPS4and its exchange interaction in contact with NiFe - Ding, Shilei; Peng, Yuxuan; Xue, Mingzhu; Liu, Zhou; Liang, Zhongyu; Yang, Wenyun; Sun, Yunbin; Zhao, Jianjun; Wang, Changsheng; Liu, Shunquan; Han, Jingzhi; Yang, Jinbo (Journal of physics. Condensed matter, 2020)
The magnetic phase diagram of the two-dimensional van der Waals magnet CrPS4and the exchange bias effect of CrPS4in contact with NiFe film have been investigated. Based on the magnetic measurements, we figure out the relatively low spin-flop field and spin-flip field for CrPS4, both of the spin transition phenomena are strongly affected by the temperature. The perpendicular exchange bias effect is studied in CrPS4single-crystal flake covered with 5 nm NiFe. Meanwhile, the variation of the cooling field has a great influence on the exchange bias field and coercivity, which is mainly attributed to the competition between the Zeeman energy and the exchange coupling at the interface as well as the formation of the multi-domain state.The magnetic phase diagram of the two-dimensional van der Waals magnet CrPS4and the exchange bias effect of CrPS4in contact with NiFe film have been investigated. Based on the magnetic measurements, we figure out the relatively low spin-flop field and spin-flip field for CrPS4, both of the spin transition phenomena are strongly affected by the temperature. The perpendicular exchange bias effect is studied in CrPS4single-crystal flake covered with 5 nm NiFe. Meanwhile, the variation of the cooling field has a great influence on the exchange bias field and coercivity, which is mainly attributed to the competition between the Zeeman energy and the exchange coupling at the interface as well as the formation of the multi-domain state.